Solution processed organic solar cells based on A–D–D′–D–A small molecule with benzo[1, 2-b:4, 5-b′]dithiophene donor (D′) unit, cyclopentadithiophene donor (D) and ethylrhodanine acceptor unit having 6% light to energy conversion efficiency1. Issue 9 (7th March 2015) - Kumar, Challuri Vijay; Cabau, Lydia; Koukaras, Emmanuel N.; Viterisi, Aurelien; Sharma, Ganesh D.; Palomares, Emilio
<x xml:space="preserve">Abstract</x> Devices based on BDT(CDTRH)2:PC71BM processed from CF and DIO (3% v)/CF exhibit PCE of 4.58% and 6.07%.